A Meta-Analysis of Plyometric Training in Female Youth: Its Efficacy and Shortcomings in the Literature. Issue 7 (July 2019) - Moran, Jason; Clark, Cain C.T.; Ramirez-Campillo, Rodrigo; Davies, Michael J.; Drury, Benjamin
Abstract : Abstract: Moran, J, Clark, CCT, Ramirez-Campillo, R, Davies, MJ, and Drury, B. A meta-analysis of plyometric training in female youth: its efficacy and shortcomings in the literature. J Strength Cond Res 33(7): 1996–2008, 2019—This meta-analysis characterized female youths' adaptability to plyometric training (PT). A second objective was to highlight the limitations of the body of literature with a view to informing future research. Fourteen studies were included in the final analysis. The effect size (ES = Hedges' g ) for the main effect of vertical jump performance was "small" (ES = 0.57, 95% confidence interval: 0.21–0.93). Effect sizes were larger in younger (<15 years; ES = 0.78 [0.25–1.30] vs. 0.31 [−0.18 to 0.80]), shorter (<163 cm; ES = 1.03 [0.38–1.68] vs. 0.25 [−0.20 to 0.70]), and lighter (<54 kg; ES = 1.14 [0.39–1.89] vs. 0.26 [−0.15 to 0.67]) participants. Programming variables seemed to influence adaptive responses with larger effects in interventions which were longer (8 weeks; ES = 1.04 [0.35–1.72] vs. 0.24 [−0.11 to 0.59]), had greater weekly training frequency (>2; ES = 1.22 [0.18–2.25] vs. 0.37 [0.02–0.71]), and whose sessions were of longer duration (≥30 minutes ES = 1.16 [0.14–2.17] vs. 0.33 [0.03–0.63]). More than 16 sessions per program (0.85 [0.18–1.51]) was more effective than exactly 16 sessions (0.46 [0.08–0.84]) which, in turn, was more effective than less than 16 (0.37 [−0.44 to 1.17]). These findings can inform the prescription of PT in female youth.